Analysis of use and land occupation of rural settlements of the municipality of Conceição do Araguaia - PA (1985 - 2020) (Research, Society and Development, 2022)
To meet the consumption needs of society, changes to the environment are inevitable in its natural configuration over the years, with these evolutionary changes in the use of areas for the production of products to be consumed, the forms of land use and occupation are characterized. In this premise, human actions on the environment are at the heart of socio-environmental problems. In the Brazilian Amazon and in the region of Conceição do Araguaia – Pará, the process of use and occupation soil is greatly influenced of agribusiness practices that over the past thirty-five years grew significantly in the region and in the areas of Settlement Projects - PAs. This study aims to comparatively analyze how was the evolution of deforestation within the Settlements in relation to areas outside PAs in the municipality of Conceição do Araguaia-PA, from 1985 to 2020, by collecting data from the Mapbiomas platform, which uses remote sensing techniques to produce maps of land use and occupation. It was found that the loss of native vegetation within the PA áreas was considerably higher in proportion, over the 35 years (56%) in relation to forest loss in areas outside the assessed municipality (43%), following the same constant of the gradual increase of forest loss and regularization of the PAs by INCRA. So there is an influence of rural settlements in the increase in deforestation in the territory of the municipality of Conceição do Araguaia - PA.